2016
DOI: 10.1111/jdi.12596
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of glycated hemoglobin, and fasting and postprandial hyperglycemia in type 2 diabetes mellitus patients in Malaysia

Abstract: Aims/IntroductionStudies on the relative contributions of fasting and postprandial hyperglycemia (FH and PPH) to glycated hemoglobin (HbA1c) in patients with type 2 diabetes have yielded inconsistent results. We aimed to assess the relationship by using continuous glucose monitoring in a multi‐ethnic cohort.Materials and MethodsA total of 100 adults with type 2 diabetes were assessed with 6‐day continuous glucose monitoring and HbA1c. Area under the curve (AUC) ≥5.6 mmol/L was defined as AUCTOTAL. AUC equal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Furthermore, glycemic features explained a much larger proportion of the variation in those with T2D than in the non-diabetic population. Other studies using CGM for assessment of glycemia under free-living conditions have also found equal contributions of fasting and postprandial hyperglycemia to HbA 1c in patients with T2D, but with a tendency of a greater contribution of PPG at lower HbA 1c concentrations and higher contribution of fasting hyperglycemia at higher HbA 1c concentrations 24 26 . The latter result is in accordance with the findings by Monnier et al 9 who suggested that the relative contribution of PPG decreased, whereas the relative contribution of fasting glucose increased, from the lowest to the highest HbA 1c quintile among non-insulin-treated T2D patients with HbA 1c ranging from ~6 to 12% (42–108 mmol/mol).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, glycemic features explained a much larger proportion of the variation in those with T2D than in the non-diabetic population. Other studies using CGM for assessment of glycemia under free-living conditions have also found equal contributions of fasting and postprandial hyperglycemia to HbA 1c in patients with T2D, but with a tendency of a greater contribution of PPG at lower HbA 1c concentrations and higher contribution of fasting hyperglycemia at higher HbA 1c concentrations 24 26 . The latter result is in accordance with the findings by Monnier et al 9 who suggested that the relative contribution of PPG decreased, whereas the relative contribution of fasting glucose increased, from the lowest to the highest HbA 1c quintile among non-insulin-treated T2D patients with HbA 1c ranging from ~6 to 12% (42–108 mmol/mol).…”
Section: Discussionmentioning
confidence: 86%
“…It is argued that postprandial plasma glucose level is more reflective of glucose control than fasting plasma glucose, thus this may be more useful for monitoring diabetic patients ( Shahram and Nargess, 2008 ; Min Park et al, 2009 ; Lim et al, 2017 ). The elevated postprandial glucose level is considered an independent risk factor for the development of macrovascular complications associated with diabetes and impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, HbA1c is not correlated with FBG in subjects without diabetes [15]. Some studies have shown that with the increase of HbA1c, the contribution of postprandial blood glucose excurses, while the contribution of FBG increses [1618].…”
Section: Discussionmentioning
confidence: 99%